Mainstream Optimization Strategies for Cathode Materials of Sodium‐Ion Batteries. Issue 4 (20th February 2022) - Xu, Huan; Yan, Qi; Yao, Wenjiao; Lee, Chun-Sing; Tang, Yongbing
Abstract : Sodium‐ion batteries are promising candidates for grid‐scale energy storage due to its abundance and similarities to lithium‐ion batteries, whereas the lack of ideal cathode materials limits their practical development. Apart from exploring novel materials, applying optimization strategies on existing potential cathode materials is demonstrated to be effective and efficient in improving their electrochemical properties toward their theoretical best capabilities. Reported strategies include element doping, surface coating, morphology and structure design, defect engineering, etc. Herein, focusing on oxide and polyanionic cathode materials, a comprehensive and systematic review on emerging optimization strategies is provided by discussing representative studies of each. Corresponding fundamental principles, their applicable ranges, and common influences on properties are analyzed. Finally, the perspectives on the current impediments and future directions in the field are presented. Abstract : The is review presents a comprehensive analysis of the mainstream optimization strategies for cathode materials of sodium‐ion batteries, including element doping, surface coating, morphology control, and specific structure design. By offering representative studies, the latest progress of oxides and polyanionic cathodes is overviewed, along with the assessment of their advantages and disadvantages. Future research orientations are thereby identified and proposed.